Relationship with clinical features of the male dependent patients and their parent’s attachment style and locus of control - Nurmedov, Serdar; Darcin, Aslı E.; Erol, Turgut Can; Noyan, Onur; Yılmaz, Onat; Dilbaz, Nesrin; Tarhan, Nevzat (Journal of Dependence, 2015)
Objective: The aim of this study was to investigate the relationship between clinical characteristics of male substance abuse patients and their parents and their attachment styles and loci of control.Methods: Forty-six outpatients and their parents were admitted to this study. All participants were diagnosed as having substance use disorder (SUD) based on DSM-IV TR. Data were gathered by means of the researcher-prepared Information Form, the Adult Attachment Style Questionnaire, and the Rotter Internal-External Locus of Control Scale. The study was approved by the Ethical Committee of Uskudar University.Results: All of the patients were male; mean age was 27.54 (±7.07). A statistically significant relationship between the attachment styles of parents and patients was found (χ2 = 12.081, p = 0.017). No statistically significant relation was found between the method of admission to the hospital and participants’ loci of control.Conclusion: In conclusion, a patient’s attachment style is related to that of his parents. It is suggested that, despite a patient’s high internal locus of control, those who reported that they sought treatment at the request of their family were either negatively impacted by their parents’ actions, or perhaps by previous counsel regarding addiction, resulting in a lowering of the patient’s desire to seek help.
Keywords: Addiction; attachment styles; parental; locus of control